Metodología para el diseño de un sistema de energía híbrido con enfoque didáctico: estudio de caso Centro Educativo Luis López de Mesa - Zambrano Joya, Diego Alejandro; Rodríguez Salazar, David Leonardo; Rodríguez Patarroyo, Diego Julián (Ingeniería, 2022)
Context: The case study presented is the product of a methodological proposal to design a hybrid energy system with a didactic approach for schools in rural areas that are not interconnected or with intermittent electricity flow. The methodology is designed to be applied in communities without advanced knowledge in renewable energies. Method: Initially the hybrid energy system is designed through dimensioning based on the acquisition of information and energy characterization of the educational community. The second phase is to determine, through the teaching processes, a model of structural blocks that allows addressing the design of a hybrid energy system as a didactic tool. The third phase consists of developing the structural blocks model for the case study of the Luis López de Mesa educational center, establishing the scope and benefits of the proposed methodology. Results: Through wind and solar energy resources, the design of the hybrid energy system is able to satisfy the energy requirement and reduce the negative environmental impact. In turn, the teaching body manifests a high interest in the theoretical-didactic learning component that bases the methodological proposal of this research, supported by the contribution of an illustrative brochure that functions as a didactic tool. Conclusions: By evaluating the methodology, it was possible to provide a support tool for the development of didactic practices taught by teachers, fostering and promoting the use of renewable energies in the structuring of curricular networks, contributing to the growth of human and environmental values ​​in the elementary school student community.